Integritas dan Akuntabilitas dalam Pengelolaan Keuangan Sekolah atau Madrasah - Nor Mubin (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2018)
The issue of integrity and accountability has recently been increasingly discussed with the demands of the community for the importance of quality education, in accordance with the provisions in SBM. Integrity is acting consistently in accordance with organizational values ??and policies as well as professional code of ethics, even in circumstances that are difficult to do, "only words with deeds". its function is as the Cognitive Function of Integrity which includes moral intelligence and self insight. While self insight itself includes self knowledge and self reflection. Means, integrity functions to change one's moral or character which then pushes him to have broad knowledge. Affective functions of integrity which include conscience and self regard. Accountability is an obligation to provide accountability and explain the performance and actions of the organization's organizers to those who have the right or obligation to request information or accountability. The smaller the participation of stakeholders in the management of schools, the lower the accountability of schools. The Asian Development Bank (ADB) confirms the general consensus that good governance is based on 4 pillars namely; accountability, transparency, predictability and participation.